Integrasi Kecerdasan Buatan (Artificial Intelligence)Dalam Pembelajaran SD dan PAUD - Dafar Dafar (CV. SINAR HOWUHOWU, 2026)
The rapid development of artificial intelligence (AI) has significantly influenced the educational sector, including primary education and early childhood education (ECE). The integration of AI in learning processes has the potential to support adaptive, interactive, and learner-centered instruction. This study aims to analyze the integration of artificial intelligence in primary school and early childhood education learning, focusing on the level of utilization, teacher readiness, challenges, and educational implications. The research employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through questionnaires, while qualitative data were obtained through interviews and classroom observations. The findings indicate that primary school and ECE teachers have begun to utilize AI-based technologies as learning media, although the level of integration remains moderate. Teachers perceive AI as a supportive tool that enhances student motivation; however, challenges persist regarding technical competence, pedagogical readiness, and ethical concerns. The study highlights the need for policy support, continuous professional development, and ethical implementation to ensure effective and sustainable AI integration in basic education.